Development of activated endothelial targeted high-density lipoprotein nanoparticles - Yu, Minzhi; Hong, Kristen; Adili, Reheman; Mei, Ling; Liu, Lisha; He, Hongliang; Guo, Yanhong; Chen, Y. Eugene; Holinstat, Michael; Schwendeman, Anna (Frontiers in Pharmacology, 2022)
Endothelial inflammation is an important pathophysiological driving force in various acute and chronic inflammatory diseases. High-density lipoproteins (HDLs) play critical roles in regulating endothelial functions and resolving endothelial inflammation. In the present study, we developed synthetic HDLs (sHDLs) which actively target inflamed endothelium through conjugating vascular cell adhesion protein 1 (VCAM-1) specific VHPK peptide. The active targeting of VHPK-sHDLs was confirmed in vitro on TNF-α activated endothelial cells. VHPK-sHDLs presented potent anti-inflammatory efficacies in vitro through the reduction of proinflammatory cytokine production and inhibition of leukocyte adhesion to activated endothelium. VHPK-sHDLs showed increased binding on inflamed vessels and alleviated LPS-induced lung inflammation in vivo. The inflamed endothelium-targeted sHDLs may be further optimized to resolve endothelial inflammation in various inflammatory diseases.